Assessment of genetic variation in Schizothorax Esocinus Heckel, 1838 from Dal and Manasbal lakes of Kashmir - UL-ARAB, NAFATH-; AHMAD, IRFAN; SHAH, TASADUQ H; BHAT, FAROOZ A; BHAT, BILAL A; YOUSUF, ZARKA; BAZAZ, ASIM IQBAL; RAZAK, NAKEER (The Indian Journal of Animal Sciences, 2022)
Schizothorax esocinus (Churru snow trout) Heckel, 1838 is a key freshwater species in the valley of Kashmir. The present study aimed to evaluate the genetic variability in the fish from the two eminent lakes of Kashmir valley namely Dal and Manasbal lakes, having different trophic gradients using biochemical (genetic) marker (SDSPage). The electrophoretic analysis revealed 6 bands of molecular weights ranging from 13 to 150 kDa for Dal lake and 8 bands of molecular weights ranging from 15 to 150 kDa for Manasbal lake. The Rf value ranged from 0.15321 to 0.70625 for sampled fishes of Dal lake and from 0.14231 to 0.63559 for sampled fishes of Manasbal lake. The study provided some basic information about the genetic variation of S. esocinus populations in the Dal and Manasbal lakes. Electropherogram studies revealed that the studied populations of Schizothorax esocinus show some degree of variation in the electrophoretic migration of muscle proteins. Polymorphism in muscle protein is clearly demonstrated among this group of fishes from the two lakes.